Modern weapons and military equipment for issue 4-2022 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Russia Developing Anti-Ship Ballistic Missile: Report; Russia’s Only Pump-Jet Kilo Class Submarine Is Back To Attack Ukraine.